The probability tutoring book an intuitive course for engineers and scientists (and everyone else!) - Ash, Carol (IEEE Press, 1993)
A self-study guide for practicing engineers, scientists, and students, this book offers practical, worked-out examples on continuous and discrete probability for problem-solving courses. It is filled with handy diagrams, examples, and solutions that greatly aid in the comprehension of a variety of probability problems.